Communicating across cultures - Ting-Toomey, Stella; Tenzin Dorjee (The Guilford Press, 2019)
"Description: This highly regarded text--now revised and expanded with 50% new material--helps students and professionals mindfully build their knowledge and competencies for effective intercultural communication on any setting. The authors' comprehensive, updated theoretical framework (integrative identity negotiation theory) reveals how both verbal and nonverbal communication are affected by multilayered facets of identity. Written in a candid, conversational style, the book is rich with engaging examples illustrating cultural conflicts and misunderstandings that arise in workplace, educational, interpersonal, and community contexts. Readers learn how to transform polarized conversations into successful intercultural engagements by combining culture-specific knowledge with mindful listening and communication skills. Key Words: intercultural communication, cross-cultural communication, human communication, communication skills, cultural competence, ethnic relations, ethnic studies, multicultural counseling, international business relations, cultural diversity, cross-cultural psychology, ethnography, mindful communication, mindfulness, intergroup communication, integrative identity negotiation theory, acculturation, adjustment, immigration, immigrants, listening skills, textbooks, texts, college classes, college courses, college students, undergraduates, graduates, foreign students, refugees, social psychology, sociolingustics, international competence"-- Provided by publisher.